Research design - Juni, Muhamad Hanafiah; Mohd Zulkefli, Nor Afiah (Community Health Society Malaysia, 2014)
Research design is a systematic study plan used to turn a research question (research questions) into a “experimental” or research project, it is specify the methods and procedures for collecting and analyzing the needed information. There are two basic types of a research methodologies, which are then further sub-categorized into various types of research designs; quantitative research method and qualitative research method. Quantitative research method is a formal, objective, systematic process in which numerical data are obtained and used to make conclusion about the subject or subjects of study. Quantitative research will answer questions on what, when and where of the research questions. On the other hand qualitative research method used a systematic subjective approach to describe life experiences, and qualitative research will answer questions on how and why of research questions. Both of the research methodologies have their own strengths and weaknesses, and for certain circumstances each the methods may complement each others.